Gamma Irradiation on Growth and Development of Amorphophallus muelleri Blume. - Santosa, Edi; Pramono, Sigit; Mine, Yoko; Sugiyama, Nobuo (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACT Iles-iles (Amorphophallus muelleri Blume) produces apomictic seeds lead to low genetic variation. In order to induce genetic variation, germinated seeds were exposed to Gamma irradiation (Co-60) at doses of 10 to 100 Gy. Seed irradiation was conducted at Center for the Application of Isotope and Irradiation Technology -National Nuclear Energy Agency (CAIRT), Indonesia. Morphology and yield of M1 generation were observed. Results showed that irradiation at a dose of 10 Gy close to LD50 with survival rate 56%. Gamma irradiation at a dose of 10 Gy delayed seeds germination. Germination rates gradually increased and reached maximum at 4 weeks after planting (WAP) for control plants, and 14 WAP of irradiated plants. At 16 WAP, germination rate of 10 Gy irradiated plants was 56% and 84% for those of control plants. Irradiation induced chimera as indicated by short petiole, variegated and abnornal shape of leaflets. Some irradiated plants entered dormancy at 8-10 weeks later than control ones. Prolong vegetative periode lead the plants to produce heavier corms. This study revealed the possibility to induce variation of A. muelleri by using gamma irradition. Keywords: Amorphophallus muelleri, gamma irradiation (Co-60), morphological variation, mutation breeding